Evaluation of the Therapeutic Effect of Propranolol Treatment in Our Patients with Infantile Hemangioma (Annals of Medical Research, 2021)
Aim: Infantile hemangiomas (IH) are the most common vascular tumors of infancy. Any treatment is not recommended to cases with İH without vital organ compression, bleeding, infection, ulceration and cosmetic problems. However, corticosteroids, propranolol, alpha-interferon, vincristine, laser surgery, or conventional surgery can be used to patients with mentioned problems in order to reduce tumor size and to eliminate complications.
Keywords: Infantile Hemangiomas; Propranolol; Treatment Response.